Islam k azeem gerneral - Safdar shaheen (Ferozesons; Lahore, 2000)
"Islam ke Azeem General" highlights the valor, leadership, and unwavering faith of the great Muslim generals, exploring their strategic brilliance and their profound impact on Islamic history.